2007
DOI: 10.1177/0267659108091337
|View full text |Cite
|
Sign up to set email alerts
|

Insensible water loss from the Jostra Quadrox D oxygenator: an in vitro study

Abstract: Extracorporeal membrane oxygenation (ECMO) has been shown to improve outcomes in neonatal patients with respiratory and/or cardiac failure. Insensible water loss is defined as water loss via evaporation from the skin and respiration. Fluid and electrolyte balance are a primary concern and very challenging in the neonatal patient population. Hypernatremia can result from untreated insensible water loss, leading to possible cerebral complications. A new type of fiber used in the Jostra Quadrox D oxygenator has r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
(26 reference statements)
3
11
0
Order By: Relevance
“…Where a disconnect between the observation of a problem’s occurrence and the response to that particular problem may occur is if the problem is not expected or the clinician cannot highlight the cause. Water loss from an ECMO oxygenator, although previously described, 4-6 remains a potentially unexpected cause of hypernatraemia in the ECMO/ICU patient. As discussed earlier, the neonatal population is very susceptible to an uncompensated free water loss due to their proportionally small circulating volume in comparison to the amount of water lost over a 24-hour period.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Where a disconnect between the observation of a problem’s occurrence and the response to that particular problem may occur is if the problem is not expected or the clinician cannot highlight the cause. Water loss from an ECMO oxygenator, although previously described, 4-6 remains a potentially unexpected cause of hypernatraemia in the ECMO/ICU patient. As discussed earlier, the neonatal population is very susceptible to an uncompensated free water loss due to their proportionally small circulating volume in comparison to the amount of water lost over a 24-hour period.…”
Section: Discussionmentioning
confidence: 87%
“…The daily loss we recorded, using the Hilite ® 2400LT PMP membrane, was 72.4 ml/day per L/min/gas flow. Camacho et al 4 recorded 72ml/day per L/min/gas flow, utilising a silicone membrane, Alexander et al 5 reported 83 ml/day with a microporous, hollow-fibre membrane, and Lawson and Holt 6 measured 48 ml/day with the PMP membrane within the Quadrox D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six MHF patches were affixed with polycin/vorite glue (60% Polycin, 40% Vorite by mass, Cas Chem) in a 50 mL conical tube. PMP MHFs were chosen due to an asymmetric geometry, which is attractive for its resistance to plasma weeping and would theoretically not experience increased plasma weeping if made hydrophilic by surface modification to support cell adhesion (Khoshbin et al, 2005;Lawson and Holt, 2007;Toomasian et al, 2005). Select groups of fiber patches were exposed to radio frequency glow discharge (RFGD; March Plasma Systems, Concord, CA) treatment while in the conical tube (0.3 Torr vacuum and ammonia gas for 60 s at 100 W).…”
Section: Surface Modification Of Mhfs To Support Endothelial Cell Growthmentioning
confidence: 99%
“…5 However, it requires an extrinsic heat exchanger, which significantly increases the priming volume of the circuit. While hollow-fiber membrane oxygenators have had complications with plasma leakage, 6 the newer Quadrox-iD Pediatric oxygenator (Maquet, Inc. Wayne, NJ, USA), recently approved by the FDA, utilizes tight hollow-fiber membranes made of polymethylpentene to eliminate plasma leakage as well as the formation of micro-bubbles. It has advantages of high gas exchange and biocompatible coating, which reduces clotting activity, thrombus formation, and complement activation [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%